A rotor speed estimation algorithm in variable speed permanent magnet synchronous generator wind energy conversion system. (4th July 2012) - Thongam, Jogendra Singh; Beguenane, Rachid; Tarbouchi, Mohammed; Okou, Aime Francis; Merabet, Adel; Fofana, Issouf; Bouchard, Pierre
SUMMARY A rotor speed estimation algorithm in a direct vector controlled permanent magnet synchronous generator wind energy conversion system is proposed. The proposed method is based on a simple equation obtained from the flux model of the machine and contains only stator flux and current. Constant gain recursive least squares estimator is used for implementing the speed estimation algorithm. Rotor position information used for coordinate transformation is computed using the estimated speed. Stator flux information required by the speed estimator is obtained using the stator voltage equation by implementing a programmable low pass filter. The estimated speed is used as the feedback signal for the speed control loop of the vector controlled machine side converter control system whose command speed is obtained from a wind speed sensorless maximum power point tracking controller, thus, we obtain a complete rotor speed and wind speed sensorless permanent magnet synchronous generator wind energy conversion system. Simulation is carried out to validate the performance of the proposed method. Copyright © 2012 John Wiley & Sons, Ltd.